Human Resource Management Practices and Corporate Entrepreneurship: An Empirical Study in Sri Lankan SMEs - Mathushan, Packiyanathan; Kengatharan, Navaneethakrishnan (Universitas Negeri Semarang, 2022)
Environmental changes and ever-increasing competition among corporations have compelled businesses to innovate incessantly. Over the few decades, the concept ‘corporate entrepreneurship’ has gained notable attention among researchers and practitioners as a salient competitive strategy that evokes a firm’s performance. Additionally, the resource-based view of the firm claims that human resources are the prominent enablers of competitive advantage. Notably, a limited but rising body of research has empirically examined the relationship between human resource management practices and corporate entrepreneurship. However, researchers wanting to draw conclusions confront a significant obstacle, as corporate entrepreneurship is not a one-dimensional concept. The overriding purpose of the study is to investigate the relationship between human resource management practices and corporate entrepreneurship. This paper uses a quantitative design; a questionnaire survey method was used to assess human resource management practices and corporate entrepreneurship. Data have been collected through a purposively chosen sample of 169 employees from various SMEs in Sri Lanka. Hypotheses were tested using a partial least squares structural equation modelling (PLS-SEM). The findings show that out of four HRM practices, three practices, viz., employee acquisition, technical training, compensation and incentives system, positively impact corporate entrepreneurship. Ironically, no significant association was found between performance appraisal and corporate entrepreneurship. Practical implications for managers are discussed at the end of the paper